Upaya Meningkatan Kinerja Melalui Supervisi Individual Terhadap Guru Sekolah Dasar Binaan Kecamatan Benua Lima Kabupaten Barito Timur - Samidi Samidi (Jurnal Simki Postgraduate, 2022)
This research is entitled Efforts to Improve Performance Through Individual Supervision of Fostered Elementary School Teachers, Benua Lima District, East Barito Regency. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and reflection. Based on the results of action research that Individual Supervision can improve the Performance of Primary School Teachers in Benua Lima District, East Barito Regency. Furthermore, the researcher recommends: (1) For school supervisors who experience the same difficulties, individual supervision can be used as a solution. (2) In order for the application of Individual Supervision to achieve maximum results, it is hoped that the School Supervisor will carry out Individual Supervision intensively and continuously.